Poloxamer-based binary hydrogels for delivering tramadol hydrochloride: sol-gel transition studies, dissolution-release kinetics, in vitro toxicity, and pharmacological evaluation - Mendonca dos Santos, Ana Claudia; Santos Akkari, Alessandra Cristina; Silva Ferreira, Iasmin Rosanne; Maruyama, Cintia Rodrigues; Pascoli, Monica; Guilherme, Viviane Aparecida; Paula, Eneida de; Fraceto, Leonardo Fernandes [UNESP]; Lima, Renata de; Melo, Patricia da Silva; Araujo, Daniele Ribeiro de (Dove Medical Press Ltd, 2015)
In this work, poloxamer (PL)-based binary hydrogels, composed of PL 407 and PL 188, were studied with regard to the physicochemical aspects of sol-gel transition and pharmaceutical formulation issues such as dissolution-release profiles. In particular, we evaluated the cytotoxicity, genotoxicity, and in vivo pharmacological performance of PL 407 and PL 407-PL 188 hydrogels containing tramadol (TR) to analyze its potential treatment of acute pain. Drug-micelle interaction studies showed the formation of PL 407-PL 188 binary systems and the drug partitioning into the micelles. Characterization of the sol-gel transition phase showed an increase on enthalpy variation values that were induced by the presence of TR hydrochloride within the PL 407 or PL 407-PL 188 systems. Hydrogel dissolution occurred rapidly, with approximately 30%-45% of the gel dissolved, reaching similar to 80%-90% up to 24 hours. For in vitro release assays, formulations followed the diffusion Higuchi model and lower K-rel values were observed for PL 407 (20%, K-rel = 112.9 +/- 10.6 mu g . h(-1/2)) and its binary systems PL 407-PL 188 (25%-5% and 25%-10%, K-rel = 80.8 +/- 6.1 and 103.4 +/- 8.3 mu g.h(-1/2), respectively) in relation to TR solution (K-rel = 417.9 +/- 47.5 mu g.h(-1/2), P<0.001). In addition, the reduced cytotoxicity (V79 fibroblasts and hepatocytes) and genotoxicity (V79 fibroblasts), as well as the prolonged analgesic effects (>72 hours) pointed to PL-based hydrogels as a potential treatment, by subcutaneous injection, for acute pain.
Keywords: micelle; cytotoxicity; genotoxicity; analgesia